Online Sexual Violence - Bulut, Burak; Kar, Hakan; Gamsız Bilgin, Nursel; Dokgöz, Halis (The Bulletin of Legal Medicine, 2023)
Objective: The use of sexually explicit correspondence and images for sexual threats has become widespread today with the increasing use of social media platforms. In our study, it is aimed to retrospectively examine the victims of online sexual violence, to discuss them in the light of the literature and to draw attention to the potential risks of social media use. Methods: The sociodemographic characteristics, social media platforms and types of online violence of the victims, their families and suspects/ perpetrators who applied to the Forensic Medicine Clinic between 01.01.2016 and 31.12.2020 were examined. Results: 35 cases were included in the study. Thirty-two victim were female and 3 victim were male. The average age of the victims was 15. 94±2,98. The age range of the victims was 11-26 years. Nineteen victims were exposed to nude photos/videos, 15 victims were exposed to sexually explicit conversations. Victims were exposed to online violence via Whatsapp (14), Facebook (7), Instagram (6), Twitter (1) and Snapchat (1). 10 victims were threatened to share nude photos/videos via social media platforms. Conclusion: Online sexually explicit conversation and sexually explicit photo/video sharing has emerged as a new type of violence with the increasing use of social media. It is necessary to organize training programs for children and adolescents and their parents about safe internet and social media use, and to raise awareness of the society about online risk factors and precautions to be taken.